Feasibility Study of a Novel Thoraco-abdominal Aortic Hybrid Device (SPIDER-graft) in a Translational Pig Model. (February 2018) - Debus, Eike S.; Kölbel, Tilo; Duprée, Anna; Daum, Günter; Sandhu, Harleen L.; Manzoni, Daniel; Wipper, Sabine H.
Abstract : Background: The hybrid SPIDER-graft consists of a proximal descending aortic stent graft and a conventional six branched Dacron graft for open abdominal aortic repair. Technical feasibility with regard to avoiding thoracotomy and extracorporeal circulation (ECC) during thoraco-abdominal aortic hybrid repair and peri-procedural safety of this novel device are unknown. Material and methods: This was a feasibility and safety study in domestic pigs (75–85 kg). The abdominal aorta including iliac bifurcation, left renal artery, and visceral arteries were exposed via retroperitoneal access. The right iliac branch was first temporarily anastomosed end to side to the distal aorta via partial clamping. During inflow reduction and infra-coeliac cross-clamping, the coeliac trunk (CT) was divided and the proximal stent graft portion of the SPIDER-graft was deployed into the descending aorta via the CT ostium. Retrograde visceral and antegrade aorto-iliac blood flow was maintained via the iliac side branch. The visceral, renal, and iliac arteries were sequentially anastomosed, finally replacing the first iliac end to side anastomosis. Technical success, blood flow, periods of ischaemia, and peri-procedural complications were evaluated after intra-operative completion angiography and post-operative computed tomography angiography. Results: Six animals underwent successful thoracic stent graft deployment and distal open reconstruction without peri-operative death. The median thoracic graft implantation time was 4.5 min, and the median ischaemia times before reperfusion were 10 min for the CT, 8 min for the superior mesenteric artery, 13 min for the right renal artery, and 22 min for the left renal artery. Angiography demonstrated appropriate graft implantation and blood flow measurements confirmed sufficient blood flow through all side branches. Conclusion: In this translational pig model, thoraco-abdominal hybrid repair using the novel SPIDER-graft was successful in avoiding thoracotomy and ECC. Technical feasibility and safety appear promising, but need to be reassessed in humans.